Optimalisasi Media Sosial Tiktok Sebagai Media Promosi UPT Perpustakaan Institut Agama Islam Negeri Madura - Ardiansyah Ardiansyah (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Purpose Research. This research aims to find out how to optimize social media Tiktok as a promotional media for UPT Library of the Madura State Islamic Institute. Methods. Qualitative research methods with a case study approach are used in this research method. Results. The result of this research is optimizing social media Tiktok as a media promotion carried out by the UPT Library of the Madura State Islamic Institute which sees increasingly advanced technological developments, making libraries have to maintain their existence, especially in terms of promoting libraries through social media Tiktok. Currently, Tiktok social media is an easy information dissemination tool and provides many benefits for Tiktok UPT Library of the Madura State Islamic Institute in promoting its library. Conclusions. By utilizing the features in it, the content or activities in the library can be promoted. The Iain Madura library received a good response in using TikTok as a place to promote the library, in the form of likes, comments, and views  even views of content on TikTok, reaching 368 views. Increasing the competence of librarians is also needed in terms of being content creators because with that social media Tiktok as a library promotion is even more advanced. Keywords: Tiktok Social Media; Promotion; UPT Library of IAIN Madura